The Book of Resemblances Remains to be Written - Joseph Guglielmi (Studies in 20th & 21st Century Literature, 1987)
The Book of Resemblances Remains to be Written. From La Ressemblance Impossible: Edmond Jabès
Keywords: Edmond Jabès